Distributed Operating System Security and Reliability - Stella, Attah; Taylor, O.E (International Journal of Computer Sciences and Engineering, 2022)
Major security issues in distributed operating systems are categorized into information leakage via hacking, server redundancy, vulnerability and risk assessment inefficiency. This study presents a systematic survey of security and reliability issues in a distributed operating system. A distributed operating system is a unique system program which adopts numerous central processors for real-time execution of allocated tasks. A distributed operating system connects many computer systems using a single communication channel. The frequent application of distributed operating systems to data sharing and management among cooperate entities has necessitated the need for distributed resources and computing strategies. The security and reliability features of a distributed operating system are critical and highly indispensable. Data security models for reliability of a distributed operating system were analysed, compared and discussed in the study. The essence of the discussed models was to enhance the performance of distributed operating systems. The study looked at models such as data-at-rest security model, access control model, steganography model, body area model, data classification model and cryptography model. The models were adequately compared and analysed especially in terms of performance mode, pros and cons. The study could be beneficial to developers of distributed operating systems and researchers with keen interest in the study area.